PROSES BERPIKIR MAHASISWA DALAM MEMBUKTIKAN PROPOSISI: KONSEPTUALISASI-GAMBAR - Lathiful Anwar; Syaiful Hamzah Nasution; Sudirman Sudirman; Susiswo Susiswo (Jurnal Kajian Pembelajaran Matematika, 2018)
Evidence is an absolute feature of mathematics and a key component in mathematics education. Although the evidence is very important, the fact is that the evidence is something that is difficult to teach or learn. One of the difficulty factors is the inadequacy of conceptual concepts and the inability to use definitions to structure evidentiary structures. This paper will describe the thinking process of students in proving a geometric proposition. Four concept of image conceptualization framework is used as a tool to explore students' thinking processes in proving a geometric proposition. One student's work and vignette, FMZ, was analyzed to provide a visualization of the image-conceptualization process used by FMZ in identifying a proposition. The results of the analysis confirm that the ability to construct evidence is related to the ability to conceptualize images, find local-local conceptualizations (traits / conclusions related to one part of the image) and global conceptualization and link relational relationships between local conceptualizations and global conceptualization into a series of statements supporting propositions / conclusion which will be proven to be a series of logical statements.